2017
DOI: 10.20944/preprints201711.0026.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thyroid Disrupting Chemicals

Abstract: Endocrine disruptor compounds are exogenous agents able to interfere with a gland function, exerting their action across different functional passages, from the synthesis to the metabolism and binding to receptors of the hormone produced. Several issues such as different levels and time of exposure and different action across different ages as well as gender, make the study of endocrine disruptors still a challenge. Thyroid is very sensitive to the action of disruptors, and considering the importance of a corr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
(74 reference statements)
1
11
0
2
Order By: Relevance
“…15, 16 Higher concentrations of some EDCs have also been observed among individuals with lower socioeconomic status, 1719 greater body mass index, 20, 21 and exposure to cigarette smoke. 22 In adults, exposure to non-persistent EDCs has been associated with a variety of health effects, including waist circumference, 21, 23 obesity, 20, 21, 23, 24 Type 2 diabetes, 17, 24, 25 and cardiovascular disease, 24 as well as altered levels of reproductive hormones, 24, 26, 27 thyroid hormones, 2831 and markers of oxidative stress and inflammation. 32, 33 These potential health effects, with others under active investigation, add evidence that exposure to EDCs is an important public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…15, 16 Higher concentrations of some EDCs have also been observed among individuals with lower socioeconomic status, 1719 greater body mass index, 20, 21 and exposure to cigarette smoke. 22 In adults, exposure to non-persistent EDCs has been associated with a variety of health effects, including waist circumference, 21, 23 obesity, 20, 21, 23, 24 Type 2 diabetes, 17, 24, 25 and cardiovascular disease, 24 as well as altered levels of reproductive hormones, 24, 26, 27 thyroid hormones, 2831 and markers of oxidative stress and inflammation. 32, 33 These potential health effects, with others under active investigation, add evidence that exposure to EDCs is an important public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that antibodies made against TSH-R, DIO2, thyroglobulin, and T3 interact with chemicals bound to HSA ( Figure 1 , Figure 2 , Figure 3 and Figure 4 ). Previous models of how chemicals play a role in disrupting thyroid metabolism include binding of the chemicals with nuclear hormone receptors, orphan and neurotransmitter receptors, and direct chemical alteration of enzymatic pathways [ 24 ]. Our study identified a new mechanism through which chemicals bound to albumin lead to structural protein misfolding, which creates neoantigens that lead to the development of antibodies that bind to key target proteins of the thyroid axis through cross-reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…When differentiated from T3, there are two conformations that are independent with T4 in the outer phenyl ring structure and independent conformations in the crystal lattice. The significant distinctions between T3 and T4 structures are condensed C4’-O4’ bond contraction of the C3’-C4’-C5’ angle and an enlargement in the C3’ and carbon C5’ angles of T4 [ 24 ]. These differences may explain why antibodies made against T3 but not against T4 reacted with chemicals bound to HSA.…”
Section: Discussionmentioning
confidence: 99%
“…Ipak, laboratorijska istraživanja jedini su način da se dobiju rezultati koji bi mogli objasniti ili predvidjeti neke učinke ED-a na ljudskom organizmu, koje su uočene u kliničkoj praksi ili u epidemiološkim istraživanjima, s napomenom da se razlike ispitivanih modela moraju uzeti u obzir. In vitro i in vivo istraživanja usmjerena su na proučavanje utjecaja ED-a na smanjivanje fertilnosti (7), utjecaja na štitnjaču (8), pojavu debljine (9), na progresiju nekih bolesti, primjeri-ce šećerne bolesti (10), endometrioze (11), nekih karcinoma (12) ili imunosnih bolesti (3).…”
Section: Uvodunclassified
“…PCB-u) te nekim metalima (olovo, živa) utječe na razvoj neuroendokrinog sustava (3,41), što su pokazala istraživanja na životinjama. Kod djece se također povezuje izloženost ED-u s poremećajima kognitivnih sposobnosti i poremećajima ponašanja, primjerice smanjenim kvocijentom inteligencije, smanjenim pamćenjem, pojavom poremećaja iz autističnog spektra ili poremećaja pozornosti s hiperaktivnošću (4,8,42). Fitoestrogeni iz soje ili iz sojinog mlijeka mogu utjecati na neuroendokrini razvoj (38).…”
Section: Neuroendokrini Sustav I Endokrini Disruptoriunclassified